Downregulation of an Evolutionary Young miR-1290 in an iPSC-Derived Neural Stem Cell Model of Autism Spectrum Disorder - Dalia Moore; Brittney M. Meays; Lepakshe S. V. Madduri; Farah Shahjin; Subhash Chand; Meng Niu; Abrar Albahrani; Chittibabu Guda; Gurudutt Pendyala; Howard S. Fox; Sowmya V. Yelamanchili (Hindawi Limited, 2019)
The identification of several evolutionary young miRNAs, which arose in primates, raised several possibilities for the role of such miRNAs in human-specific disease processes. We previously have identified an evolutionary young miRNA, miR-1290, to be essential in neural stem cell proliferation and neuronal differentiation. Here, we show that miR-1290 is significantly downregulated during neuronal differentiation in reprogrammed induced pluripotent stem cell- (iPSC-) derived neurons obtained from idiopathic autism spectrum disorder (ASD) patients. Further, we identified that miR-1290 is actively released into extracellular vesicles. Supplementing ASD patient-derived neural stem cells (NSCs) with conditioned media from differentiated control-NSCs spiked with "artificial EVs" containing synthetic miR-1290 oligonucleotides significantly rescued differentiation deficits in ASD cell lines. Based on our earlier published study and the observations from the data presented here, we conclude that miR-1290 regulation could play a critical role during neuronal differentiation in early brain development.